Isovalent Cation Ordering in the Polar Rhombohedral Perovskite Bi2FeAlO6. Issue 49 (8th November 2018) - De, Chandan; Arévalo‐López, Ángel M.; Orlandi, Fabio; Manuel, Pascal; Attfield, J. Paul; Sundaresan, Athinarayanan
Abstract: Ordering of cations in different structural types occurs when there is a significant difference in the oxidation states and ionic radii of the ions involved. Herein we report an unusual ordering of isovalent cations Fe 3+ and Al 3+ in the polar rhombohedral R 3 double perovskite structure of Bi2 FeAlO6 synthesized at high‐pressure (6 GPa) and high‐temperature (1000 °C). This ordered structure is derived from the 1:1 combination of the polar oxides BiFeO3 ( R 3 c ) and BiAlO3 ( R 3c), which results in reduction of symmetry to an R 3 structure where the Fe 3+ and Al 3+ ions are ordered in a rock salt manner. However, these ions remain disordered in BiFe1− x Al x O3 ( x =0.2, 0.3, 0.4) perovskites with R 3 c structure. The ordered compound undergoes antiferromagnetic ordering at TN ≈280 K. The butterfly nature of piezoelectric displacement loop further confirms the polar nature of the cation‐ordered Bi2 FeAlO6 . Abstract : The crystal structure of the double perovskite Bi2 FeAlO6 shows a remarkably high degree of ordering of isovalent Fe 3+ and Al 3+ cations. The butterfly nature of the piezoelectric response confirms the polar structure of the material.